Updated Health and Cost Impacts of Electronic Nicotine Delivery Systems, Using Recent Estimates of Relative Harm for Vaping Compared to Smoking. Issue 3 (2nd September 2021) - Summers, Jennifer A; Ait Ouakrim, Driss; Wilson, Nick; Blakely, Tony
Abstract: Background: Measuring population health and costs effects of liberalizing access to electronic nicotine delivery systems (ENDS) is an evolving field with high persisting uncertainty. A critical area of uncertainty for policy-makers are estimates of net harms from ENDS relative to cigarettes, therefore, we model these harms using updated estimates incorporating disease specificity. Methods: We use updated estimates of relative harm of vaping vs smoking, based upon relevant biomarker studies to model the impact of liberalizing access to ENDS in New Zealand (NZ), relative to a ban (where ENDS are not legally available), in an existing proportional multi-state life-table model of 16 tobacco-related diseases. Results: This modeling suggests that ENDS liberalization results in an expected gain of 195 000 quality-adjusted life-years (QALYs) over the remainder of the NZ population's lifespan. There was wide uncertainty in QALYs gained (95% uncertainty interval [UI] = −8000 to 406 000) with a 3.2% probability of net health loss (based upon the number of simulation runs returning positive QALY gains). The average per capita health gain was 0.044 QALYs (equivalent to an extra 16 days of healthy life). Health system cost-savings were expected to be NZ$2.8 billion (US$2.1 billion in 2020 US$; 95%UI: −0.3 to 6.2 billion [2011 NZ$]), with an estimated 3% chance of a net increase in per capita cost. Conclusions: This updated modeling around liberalizing ENDs in NZ, still suggests likely net health and cost-saving benefits—but of lesser magnitude than previous work and with a small possibility of net harm to population health. Implications: This study found evidence using updated biomarker studies that ENDS liberalization could result in QALY gains across the New Zealand population lifespan that are also cost-saving to the health system. Governments should include the information from these types of modeling studies in their decision-making around potentially improving access to ENDS for existing smokers, while at the same further reducing access to tobacco.